(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Coagulants are essential in water treatment processes particularly in coagulation and flocculation for reducing suspended solids and improving water clarification. The purpose of this study is to investigate the effectiveness of plant-based coagulants from coconut husk and pandan leaves in reducing turbidity of river water. The study used jar test to determine the optimal coagulant dose and solution pH for coconut husk and pandan leaves coagulants in reducing river water turbidity with alum used as a benchmark for comparison. In addition, a comparison between these plant-based coagulants and alum was made to see the potential of the coagulants. Scanning electron microscopy (SEM) was employed to observe the morphology of the plant-based coagulants while phytochemical tests confirmed the presence of tannins and flavonoids through colorimetric observation. Results indicated that pandan leaves coagulants achieved up to 90% turbidity removal of river water at an optimal dose of 40 mg/L and pH 9, whereas coconut husk coagulant reached 60% removal at 10 mg/L and pH 4. SEM analysis revealed fibrous structures with rough surface textures, suggesting good potential for particle adsorption. Overall, both plant-based coagulants demonstrated promising performance in turbidity reduction, supporting their potential as sustainable alternatives to conventional chemical coagulants.